Evaluación de mercurio en sedimentos de quebradas con influencia de pozos petroleros en el río Corrientes - Vilela Grandez, Daniel Santos (2024)
In recent times, it has been evident in the Pastaza, Corrientes, Tigre, Marañón rivers, that oil activity of Lots 192 and 8 has generated oil sludge and the discharge of waste into bodies of water, affecting aquatic ecosystems. as a result of exploitation. Mercury is the organic compound formed in the environment by microbial metabolism and by abiotic and anthropogenic processes. By evidencing the environmental and social problems, the objective was to identify differences in mercury concentrations in sediments in streams with the occurrence and absence of oil spills in the Corrientes River. For this, sediments were collected on the banks of streams with a 120 cm tube. in two areas of the Corrientes River during 2016 and 2018 respectively: upper Corrientes (four streams: Timo Entsa, Aunts Entsa, Huayurí and Pañayacu) with oil influence and lower Corrientes (three streams, Trompeterillo, Jergón and Oleoducto) without oil influence. The data were analyzed using the EPA7474 method (ICP-AES). It was determined that there were no statistically significant differences between the concentrations of mercury in the sediment samples in the two basins of the Corrientes River (upper and lower Corrientes), however, there are two high values of mercury found in average concentrations of 0,11 and 0,10 mg. /kg in the studied areas, but they are below international standards.